Analisis Pemilihan Moda Transportasi Online dan Angkutan Konvensional - Andresta, Nanda; Sulistiyorini, Rahayu; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Transport mode choice greatly impacted by the characeristic of the passengers. The purpose of this study are to determine the factors that impacted the travel subjects and to determine the mode choice probability of online transportation and conventional transportation. Data Processing is using SPSS for regresion analysis, to determine the factors that impacted the choice mode of online taxi and conventional taxi . The result of questionnaire distribution from airport passangers are most of (71%) the passengers has choose online taxi and the rest 29% has choose conventional taxi as the transportation mode to headed Radin Inten II Airport.Based on correlation test, the variables that impacted are the fare, the convenience and the availability of mode with R square = 48,7% and generated regression equation Y = 2,233 + 0,726 X1 + 0,530 X2 + 0,700 X7.Based on logit model of first scenario, it generated probability 89,93%of online taxi and 10,07% of conventional taxi. On seond scenario, it generated probability 55,80% of online taxi and 44,20% of conventional taxi. Based on logit model scenario, it shows that the online taxi has bigger tendency for being choosen than conventional taxi and the variables are the fare (X1), the convenience (X2) and the availability (X7) of mode did not have significant impact.